Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3109/00207454.2013.836703
|View full text |Cite
|
Sign up to set email alerts
|

Clevidipine for acute hypertension in patients with subarachnoid hemorrhage: a pilot study

Abstract: Clevidipine controlled SBP in all patients with aneurysmal SAH in <22 min and kept it within the elective range 70% of the time without major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The CLASH (Clevidipine in Aneurysmal Subarachnoid Hemorrhage) study was a single-center,open-label prospective pilot study that enrolled 5 patients with aneurysmal subarachnoid hemorrhage (SAH) with BPs above a prespecified limit (set by treating physicians) requiring antihypertensive therapy. 20 All patients reached their specified SBP targets after initiation of clevidipine within 14.2 + 6.4 minutes (range 7-22 minutes) at an average infusion rate of 10.8 + 9.1 mg/h (range 2-24 mg/h). 20 ICP measurements in 2 patients with extraventricular drains did not increase after initiation of clevidipine.…”
Section: Evidence Supporting Clevidipinementioning
confidence: 90%
See 1 more Smart Citation
“…The CLASH (Clevidipine in Aneurysmal Subarachnoid Hemorrhage) study was a single-center,open-label prospective pilot study that enrolled 5 patients with aneurysmal subarachnoid hemorrhage (SAH) with BPs above a prespecified limit (set by treating physicians) requiring antihypertensive therapy. 20 All patients reached their specified SBP targets after initiation of clevidipine within 14.2 + 6.4 minutes (range 7-22 minutes) at an average infusion rate of 10.8 + 9.1 mg/h (range 2-24 mg/h). 20 ICP measurements in 2 patients with extraventricular drains did not increase after initiation of clevidipine.…”
Section: Evidence Supporting Clevidipinementioning
confidence: 90%
“…20 All patients reached their specified SBP targets after initiation of clevidipine within 14.2 + 6.4 minutes (range 7-22 minutes) at an average infusion rate of 10.8 + 9.1 mg/h (range 2-24 mg/h). 20 ICP measurements in 2 patients with extraventricular drains did not increase after initiation of clevidipine. 20 The authors concluded that clevidipine was an effective agent for BP control during SAH and postulated that SBP control may be better with clevidipine as compared to nicardipine based on historical data from their facility.…”
Section: Evidence Supporting Clevidipinementioning
confidence: 90%
“…The clevidipine in aneurysmal subarachnoid hemorrhage (CLASH) study was a singlecenter, open-label prospective pilot study that enrolled 5 patients with aneurysmal subarachnoid hemorrhage (SAH) with BPs above a prespecified limit (set by treating physicians) requiring antihypertensive therapy. 20 All patients reached their specified SBP targets after initiation of clevidipine within 14.2 + 6.4 minutes (range: 7-22 minutes) at an average infusion rate of 10.8 + 9.1 mg/h (range: 2-24 mg/h). 20 The ICP measurements in 2 patients with extraventricular drains did not increase after initiation of clevidipine.…”
Section: Evidence Supporting Clevidipinementioning
confidence: 90%
“…20 All patients reached their specified SBP targets after initiation of clevidipine within 14.2 + 6.4 minutes (range: 7-22 minutes) at an average infusion rate of 10.8 + 9.1 mg/h (range: 2-24 mg/h). 20 The ICP measurements in 2 patients with extraventricular drains did not increase after initiation of clevidipine. 20 The authors concluded that clevidipine was an effective agent for BP control during SAH and postulated that SBP control may be better with clevidipine when compared to nicardipine based on historical data from their facility.…”
Section: Evidence Supporting Clevidipinementioning
confidence: 90%
“…Clevidipine can be effectively used during elective neurosurgical procedures, including neurovascular interventions, to control the BP during intraoperatively and in the postoperative period (Bekker et al, 2010; Varelas et al, 2014). …”
mentioning
confidence: 99%